Transformation of mangiferin to norathyriol by human fecal matrix in anaerobic conditions: comprehensive NMR of the xanthone metabolites, antioxidant capacity, and comparative cytotoxicity against vancer cell lines - Souza, José R. R. de; Trevisan, Maria T.S.; Hull, William Edmund; Würtele, Gerd; Breuer, Andrea; Frei, Eva; Ulrich, Cornelia; Owen, Robert (Natural product communications, 2020)
Several natural drugs (termed prodrugs) when administered orally undergo transformation by intestinal bacteria, producing metabolites, which may be more active than the parent compound. Mangiferin (I) is reported to have very low bioavailability in the upper gastrointestinal tract and reaches the large intestine, where it may be metabolized by the indigenous bacteria. Therefore, the aim of this study was to conduct pilot anaerobic fermentation studies with fecal inocula from human volunteers (n = 3) to identify possible metabolic end products of mangiferin by the gastrointestinal metabolome. The major metabolite identified was deglycosylated mangiferin, namely, norathyriol (II) with an increase in homomangiferin (III) which was a minor contaminant of I. Mangiferin metabolites were identified and quantitated in the fermentation broths by high performance liquid chromatography (HPLC)-diode array detection-electrospray ionization-mass spectrometry, and structures confirmed unequivocally by nuclear magnetic resonance, after purification by semipreparative HPLC. Cell culture assays with 2 human cancer cell lines Caco-2 (colon cancer) and A240286S (non-small lung adenocarcinoma) showed that while the substrate mangiferin (I) and homomangiferin (III), a minor metabolite, are non-cytotoxic (half-maximal inhibitory concentration [IC50] ≥ 100 µM), the major metabolite norathyriol (II) is cytotoxic against Caco-2 cells (IC50 = 51.0 µM), whereas it is cytostatic against A240286S cells with a similar IC50 (51.1 µM).
Gesehen am 06.05.2022